1992
DOI: 10.1002/1097-0142(19920915)70:6<1585::aid-cncr2820700623>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple thyroid involvement (intraglandular metastasis) in papillary thyroid carcinoma. A clinicopathologic study of 105 consecutive patients

Abstract: Multiple thyroid involvement (MTI) in papillary thyroid carcinoma was clinicopathologically studied in 105 non‐selected, consecutive patients. Whole thyroids resected by total thyroidectomy were sectioned at intervals of 2–3 mm (mean number of slices per gland, 19.2) and histologically reviewed. The intraglandular cancer foci, other than the tumor regarded as the primary focus, were demonstrated in 82 (78.1%) of 105 patients. The foci were usually small (less than 4 mm) and were not accompanied by sclerotic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
2
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 14 publications
9
71
2
2
Order By: Relevance
“…Thyroid gland has a rich network of intraglandular lymphatics that intercommunicate between lobes through the isthmus and drain to the cervical lymph nodes. 4 Intraglandular metastasis and cervical lymph node metastasis occur through these rich lymphatic networks. Multivariate analysis showed isolated glands and lateral tubular growth to be independent risk factors for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid gland has a rich network of intraglandular lymphatics that intercommunicate between lobes through the isthmus and drain to the cervical lymph nodes. 4 Intraglandular metastasis and cervical lymph node metastasis occur through these rich lymphatic networks. Multivariate analysis showed isolated glands and lateral tubular growth to be independent risk factors for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Papillary thyroid carcinoma tends to metastasize to the cervical lymph nodes during the early stages of the disease. 4,5 Cervical lymph node metastases are found in 30-90% of patients at the time of diagnosis. 5 Nodal metastases increase the risk of loco-regional recurrence and cancer-specific mortality in older patients (445 years) and distant metastases.…”
mentioning
confidence: 99%
“…In PTCs %2 cm, the impact of multicentricity on tumor outcome is still debated. Indeed, in some studies it has been significantly correlated with disease relapse (Baudin et al 1998, Chow et al 2003, Pellegriti et al 2004, whereas in other series the association with the outcome has been found to be marginal, indicating that a more aggressive treatment is not required in case of multiple foci (Kato et al 1992, Mazzaferri & Jhiang 1994. In the present series, multicentricity was associated with a worst outcome in tumors of group B, whereas no significance was found at the multivariate analysis performed on all tumors %2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…At this point it is also worth considering the question of multicentricity of childhood DTC. In general, thyroid cancer and especially its papillary histotype appear as multiple foci (Katoh et al 1992 and recent reports (Sugg et al 1998) indicate that these foci may be polyclonal. It is generally accepted that juvenile DTC is more frequently multicentric, although detailed comparisons are hampered by technical differences.…”
Section: Characteristics and Natural History Of Juvenile Dtcmentioning
confidence: 99%